Penerapan Penerapan Media Pop Up Book dalam Menanamkan Sikap Toleransi Keberagaman Budaya dan Agama pada Siswa Kelas V SD Negeri 2 Meurandeh - Dia Nanda Putri Dabutar; Lhutfia Wahyu Safutri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study describes the application of Pop Up Book learning media in instilling tolerance toward cultural and religious diversity among grade V B students at SD Negeri 2 Meurandeh. Indonesia’s plural society requires tolerance education from an early age, yet preliminary observations showed that students’ tolerance attitudes still needed improvement. Learning was also less engaging because teaching methods were dominated by lectures and supported by limited instructional media. This research used a descriptive qualitative approach involving 23 grade V B students who were studying cultural and religious diversity in Citizenship Education. Data were collected through documentation and a psychological scale instrument consisting of 25 Likert-scale statements. The assessment covered five dimensions: active student involvement, understanding of material, group discussion ability, application of tolerance values, and motivation and learning enthusiasm. The results showed that Pop Up Book media was applied effectively. All students gave positive responses, with 100% achievement across all assessment dimensions. The three-dimensional visual elements of the Pop Up Book attracted students’ attention, increased learning motivation, and helped them understand cultural and religious diversity more easily. Therefore, Pop Up Book media can be used as an effective alternative learning medium for strengthening tolerance attitudes in elementary school learning contexts.